(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Road safety has long been considered as one of the social responsibilities to the Malaysian Government. In the visibility of this responsibilities, multiple bodies concern on road safety has been formed within the government departments, private agencies, and voluntary organizations. The current study was carried out to understand the recent trend and statistics of road motorcycles in Kajang, Malaysia. The statistics for road accidents and the related casualties in Malaysia from 2005 to 2008 was obtained from the Bukit Aman Police Headquarters. The statistics of registered motor vehicles in Malaysia will be provided by Road Transport Department of Malaysia. Data will be analyzed using SPSS software. Descriptive and hypothesis testing techniques were used to obtain the results based on the stated objectives of the study. From the crash statistics, it can be revealed that Kajang has a relatively higher incidence of casualties (dead, seriously injured and lightly injured). In addition, the results show that the young riders of motorcycles among the age of 16 to 20 years from the majority of those who die in motorcycles accidents. Moreover, it is recognized that the considerable percentage of the motorcyclists and the pillion riders did not wear safety helmets when they were traveling on the roads network. The Malaysian government has to organize many motorcycle safety campaigns in the coming few years.